A Systematic Review and Meta-Analysis of Clinical Effectiveness and Safety of Hydrogel Dressings in the Management of Skin Wounds - Zhang, Lijun; Yin, Hanxiao; Lei, Xun; Lau, Johnson N. Y.; Yuan, Mingzhou; Wang, Xiaoyan; Zhang, Fangyingnan; Zhou, Fei; Qi, Shaohai; Shu, Bin; Wu, Jun (Frontiers in Bioengineering and Biotechnology, 2019)
The purpose of this systematic review and meta-analysis is to assess the clinical effectiveness and safety of the medical hydrogel dressings used in skin wounds and therefore to weight the evidence for their clinical application. PubMed/Medline (1980-2019), Cochrane Library (1980-2019), ClinicalTrials.gov, Cochrane CENTRAL, Chinese Journal Full-text Database (CNKI, 1994-2019), and China Biomedy Medicine disc (CBM, 1978- 2019), Chinese Scientific Journal Database (VIP, 1989-2019) and Wanfang Database (WFDATA, 1980-2019) were searched to identify relevant clinical trials and studies. Forty-three studies that assessed hydrogel vs. non-hydrogel dressings were identified. Compared to the latter, hydrogel dressings associated with a significantly shortened healing time of degree II burn (superficial and deep) wounds, diabetic foot ulcers, traumatic skin injuries, radioactive skin injuries, dog bites, and body surface ulcers. In addition, hydrogel dressing obviously increased the cure rate of diabetic foot ulcers, surgical wounds, dog bites, and body surface ulcers. Moreover, hydrogel dressing significantly relieved pain in degree II burn (superficial and deep) wounds, traumatic skin injuries, and laser treatment-induced wounds. However, no significant differences obtained between hydrogel and non-hydrogel dressings in the healing time of surgical wounds, the cure rate of inpatients’ pressure ulcers, and phlebitis ulcers. This comprehensive systematic review and meta-analysis of the available evidence reveals that the application of hydrogel dressings advances the healing of various wound types and effectively alleviates the pain with no severe adverse reactions. These results strongly indicate that hydrogel products are effective and safe in wound management.